The Traditional Knowledge Protection Debate: Identifying and Listening to the Voices of Traditional Knowledge Holders - Maina, Charles Kamau (Scholarship@Western, 2009)
In 1993, the United Nations General Assembly declared 1995-2004 an International Decade of the World's Indigenous People and subsequently declared 20052014 another such decade. These declarations challenged governments and the international community to address issues, such as protection of traditional knowledge, affecting indigenous communities. This study analyses the debate on protecting traditional knowledge and tests how well international level proposals mirror grassroots perspectives of knowledge-holders. Two kinds of qualitative evidence are used: first, documentary texts generated in the various international forums were analyzed, using thematic text analysis, and, second, semi-structured interviews were conducted with elders across communities representing four linguistically distinct Canadian First Nations. The evidence indicates that international level proposals do not map onto those of the Indigenous Peoples studied and that the voices of the Indigenous Peoples studied are not gaining traction in the international forums. Findings establish that traditional knowledge holders have concerns and needs that the current international policy debates are not addressing. These concerns and needs call for a grassroots level dialogue, which is not taking place. The research questions asked are important to learning, research, and practice in a number of fields. The study emphasizes a multiplicity of worldviews about information, highlights differences in approaches to the notions of control over information and the value of information. It highlights the importance of taking into account, in all forums, knowledge holders' views and demonstrates the underlying cultural and ideological assumptions upon the basis of which examined international forums work. This research is an example of the way in which Library and Information Science (LIS) research, in particular, focuses on perspectives that should inform policy-making at all levels. The study demonstrates how the LIS tradition of insistence on focusing on ...